FULLSCREEN > Archive > 2023 > Vol 4, №5 (2023) > Principles of modern brain tumor diagnosis Principles of modern brain tumor diagnosis - Leonid B. Likhterman; Vladimir A. Okhlopkov; Marina V. Ryzhova; Galina P. Snigireva; Liudmila V. Shishkina; Igor N. Pronin; Natalia E. Zakharova; Artem I. Batalov; Valeriy N. Kornienko (LLC "MEDIAFORMAT", 2023)
The paper reports methodology of the current phase of brain tumor recognition. The World Health Organization classification of the central nervous system tumors issued in 2021 and its main differences from the previous version are provided. The molecular genetic methods, the use of which is necessary to establish the comprehensive integrated pathological diagnosis required for selection of adequate brain tumor therapy, are disclosed. The potential of using neuroimaging techniques for comprehensive brain tumor diagnosis is discussed.